Propuesta de productos turísticos para la parroquia Sabanilla, cantón Zamora, provincia de Zamora Chinchipe - Sarango Paz, Eduardo Leonel (2023)
Tourism in rural areas boosts global sustainable development. According to the World Tourism Organization (UNWTO), this trend highlights the authenticity of pictures destinations and strengthens local economies by taking advantage of natural and cultural resources. Analyzing its impact and challenges is essential to maximize benefits and mitigate implications. Therefore, the main objective of this research work was to strengthen tourism activity in the Sabanilla parish through the creation of a tourism product model as a proposal for tourism development in rural areas. Therefore, this research is entitled: "Proposal of Tourism Products for the Sabanilla Parish, Zamora Canton, Zamora Chinchipe Province". For the development of this research, three specific objectives were proposed: Diagnose the agro-tourism potential of the Sabanilla parish; Design tourism products for the Sabanilla parish; and finally: Determine marketing strategies for tourism products. The essential methodologies of this research were those of Marvin Blanco, which in addition to including a tourism diagnosis model, integrated conventional systems such as the application of SWOT, surveys and interviews. The methodology of the MINTUR's Manual for the Generation of Tourism Routes and Itineraries contributed to the generation of the tourism product proposal. Finally, an online and offline Marketing Plan was created for the established products. In addition, software was used to apply the mathematical SWOT, in order to obtain objective strategies to work in an environment where there was a lack of tourism culture, but where it was possible to change the conventional life model through tourism activity. As a final result, a record was made of the tourism resources enjoyed by the territory in question. Eleven natural resources with great potential for tourism exploitation were identified. Consequently, a model was designed for a tourist route and circuit that integrated all of the identified resources and activities, based on an adventure and experiential tourism approach.